Alice Springs Telecommunications Facilities - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2017)
Two papers from the Journal in 1939 and 1990 respectively contrasting the telecommunication facilities and lifestyles at Alice Springs.